Birth Center Breastfeeding Rates: A Literature Review. Issue 6 (November 2022) - George, Erin K.
Abstract: Introduction: Breastfeeding rates in the United States fall short of national targets and are marked by racial and ethnic disparities. Birth centers are associated with high rates of breastfeeding initiation and duration, yet no systematic review has compiled reported birth center breastfeeding data. Methods: A PRISMA-guided literature review was conducted in CINAHL, PubMed, and Web of Science to retrieve quantitative studies that reported breastfeeding data in birth centers. Inclusion criteria focused on English language studies published since 2011 with breastfeeding outcomes from birth centers in the United States. Results: Ten studies were included for analysis. Breastfeeding rates that exceeded actual and target national breastfeeding rates were reported among all 10 studies. Characteristics about breastfeeding outcomes were reported heterogeneously across the studies, which included a range of breastfeeding timepoints (immediately postpartum up to 6 weeks postpartum) and definitions of breastfeeding. Discussion: Although breastfeeding rates reported in birth centers are higher than national breastfeeding rates and targets, authors of the included studies did not explore or analyze these rates in-depth. Developing standard definitions and data collection may enhance research about breastfeeding outcomes in birth centers. Clinical Implications: Giving birth in a birth center is associated with higher than national breastfeeding rates. Abstract : Breastfeeding rates in the United States fall short of national targets and are marked by racial and ethnic disparities. There are limited data on birth center breastfeeding rates. In this PRISMA-guided literature review, breastfeeding rates that exceeded actual and target national breastfeeding rates were reported among all studies of birth centers. Giving birth in a birth center is associated with higher than national breastfeeding rates.